2012
DOI: 10.1063/1.4772404
|View full text |Cite
|
Sign up to set email alerts
|

The influence of internal rotational barriers and temperature on static and dynamic properties of bulk atactic polystyrene

Abstract: We present molecular dynamics simulations of a chemically realistic model as well as a quasi-freely rotating chain model for bulk atactic polystyrene in a temperature range from 240 to 500 K to characterize the role of temperature and internal rotational barriers on static and dynamics properties of bulk polystyrene. We demonstrate that on different length scales, the change of structure shows different behavior upon cooling, and the internal rotational barriers play a similar role as temperature in this respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
9
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 65 publications
5
9
0
Order By: Relevance
“…The results obtained from MD simulation by Harmandaris et al show the increasing effect of elevated pressure on glass transition temperature, which is in agreement with experimental measurements . Xie et al in 2012 investigated the effect of polymer backbone stiffness on the static and dynamic properties . This effect was also investigated in another study by Bulacu and Giessen within a coarse grain model .…”
Section: Introductionsupporting
confidence: 61%
See 1 more Smart Citation
“…The results obtained from MD simulation by Harmandaris et al show the increasing effect of elevated pressure on glass transition temperature, which is in agreement with experimental measurements . Xie et al in 2012 investigated the effect of polymer backbone stiffness on the static and dynamic properties . This effect was also investigated in another study by Bulacu and Giessen within a coarse grain model .…”
Section: Introductionsupporting
confidence: 61%
“…The newly proposed multiple shape memory properties of Nafion, which is accompanied by thermal phase transitions, is another example that shows the importance of investigations of thermomechanical properties and glass transition temperature at the microscopic level . Shape memory materials can be adjusted to memorize certain temporary shapes, which had been imposed during a shape fixing process and recover their permanent shape upon applied stimulus such as electric field, heat, or light.…”
Section: Introductionmentioning
confidence: 99%
“…42 By using the single-molecule uorescence microscopy, Wöll's group found that the temperature dependence of fraction of mobile molecules in polystyrene lms exhibited similar trends with that of PSM. [26][27][28][29][30][31][32] Similarly, we also observe the conformational changes during cooling in the current simulation. [26][27][28][29][30][31][32] Similarly, we also observe the conformational changes during cooling in the current simulation.…”
Section: Resultsmentioning
confidence: 58%
“…13,14 For instance, the structural characteristics of CRR are still unknown. [27][28][29][30][31][32] The increase of the fraction of transconformations may induce the formation of the short-range order in polymers. For colloidal system, Tanaka et al 23,24 and Yodh et al 25 detected the formation of some local ordered structures during cooling, and they argued that the development of the local ordered structures may be the origin of the slow dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…At the glass transition temperature, the specific volume, v , versus temperature, T , exhibits a change in slope, moving from a low value in the glassy state ( T < T g ) to a higher value in the rubbery state ( T > T g ) . Molecular dynamics can be used to determine the specific volume of the polymer at different temperatures, at a constant pressure.…”
Section: Theorymentioning
confidence: 99%